Photocatalytic hot-carrier chemistry. (January 2020) - Sun, Yugang; Tang, Zhiyong
Abstract: Abstract : Light absorption in nanoparticles of semiconductors and metals excites electrons from ground states to high-energy levels, generating hot electrons with the addition of kinetic energy, and consequently, complimentary hot holes in the nanoparticles. These hot electrons are capable of injecting themselves into the empty antibonding orbitals of chemical bonds of reactant molecules adsorbed on the surface of the nanoparticles, thereby weakening the chemical bonds to trigger corresponding desirable chemical reactions. Hot-electron chemistry represents a fundamentally different mechanism of solar-to-chemical energy conversion compared to the traditional photochemistry that relies on the direct photo-excitation of electrons in reactant molecules and thermal catalysis. This issue of MRS Bulletin examines the generation and relaxation of hot electrons in typical nanoparticle systems, and the flow of hot electrons across the surfaces of the nanoparticles. The promise of hot-electron chemistry (and the complementary hot-hole chemistry) is supported by its application in many important reactions, including CO2 reduction, water splitting, hydrogenation, and coupling reactions, highlighting its great potential in achieving high energy-conversion efficiency and product selectivity.